2005
DOI: 10.2134/jeq2004.0434
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Dietary Protein and Nonstarch Polysaccharide to Control Swine Manure Emissions

Abstract: Odor and greenhouse gas (GHG) emissions from stored pig (Sus scrofa) manure were monitored for response to changes in the crude protein level (168 or 139 g kg(-1), as-fed basis) and nonstarch polysaccharide (NSP) content [i.e., control, or modified with beet pulp (Beta vulgaris L.), cornstarch, or xylanase] of diets fed to pigs in a production setting. Each diet was fed to one of eight pens of pigs according to a 2 x 4, full-factorial design, replicated over three time blocks with different groups of animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 11 publications
4
52
1
5
Order By: Relevance
“…Hence, as N 2 O emissions are related to the amount of N in the manure, they should potentially be reduced with lower N excretion. Examining the effect of dietary protein and non-starch polysaccharide on emissions from swine manure, Clark et al (2005) found no effect of the latter, except in combination with low protein treatments. Velthof et al (2005) found that increasing non-starch polysaccharide corresponded to increasing CH 4 .…”
Section: Dietmentioning
confidence: 89%
“…Hence, as N 2 O emissions are related to the amount of N in the manure, they should potentially be reduced with lower N excretion. Examining the effect of dietary protein and non-starch polysaccharide on emissions from swine manure, Clark et al (2005) found no effect of the latter, except in combination with low protein treatments. Velthof et al (2005) found that increasing non-starch polysaccharide corresponded to increasing CH 4 .…”
Section: Dietmentioning
confidence: 89%
“…Other studies describing the impact of increased dietary fibre in the form of sugar beet on pig systems also report reduced ammonia emissions (e.g. Canh et al 1998;Fernandez et al 1999;Clark et al 2005). The overall effect on N balance depends on whether N was in surplus or deficit, because fibre reduces N digestibility but repartitions N from urine to faeces if in surplus (Morgan & Whittemore 1988) and on how the manure is stored or spread (Verge et al 2009).…”
Section: Impact Of Altered Diet and Reproductive Performance On The 'mentioning
confidence: 99%
“…On the other hand, some authors reported that odour concentration and offensiveness increased when low-CP diets supplemented with synthetic amino acids were used (Otto et al, 2003;O'Connell et al, 2006). Finally, other studies could not find differences in odour composition and magnitude when low-CP diets were used (Sutton et al, 1999;Clark et al, 2005;Leek et al, 2007).…”
Section: Dietary Manipulationmentioning
confidence: 97%
“…The increase of feed FC stimulates microbial activity in animal gut and in the manure, shifting the nitrogen balance from urine to faeces (Sutton et al, 1999;Clark et al, 2005). It has been widely demonstrated that FC incorporated into pig diets increases the volatile fatty acid (VFA) content in manure (Clark et al, 2005;Kerr et al, 2006;O'Connell et al, 2006), but it remains unclear whether the odour profile is affected. Whereas Lynch et al (2008) obtained a 41% increase of odour emissions when sugar beet pulp was added to pig diets, a non-significant effect of FC was found by Clark et al (2005) and Le et al (2007).…”
Section: Dietary Manipulationmentioning
confidence: 99%
See 1 more Smart Citation